IMPLEMENTATION OF EDUCATION MANAGEMENT WITH LEARNING MEDIA IN ERA 4.0 - Bagus Harun Al Rashid; Yuni Sara; Adiyono (ADISAM Publisher, 2022)
Era 4.0 is an era where almost everything is controlled by technology, including in the world of education. The impact of the 4.0 era in the world of education is evident in the increasing number of technology-based learning media that make it easier for an educator to convey material even without having to meet face to face. This paper examines and describes this technology- based learning media that facilitates the learning process in terms of effectiveness and efficiency. There are several learning methods that can be applied, namely in the form of a learning management system, learning content management system, and Social learning Network. Many benefits can be felt with the existence of technology-based learning media, in addition to being able to attract students' interest in learning can also improve learning achievement results. Therefore, technology-based learning media is highly expected to be utilized in the learning process.